2006
DOI: 10.1016/j.envpol.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The veterinary antibiotic oxytetracycline and Cu influence functional diversity of the soil microbial community

Abstract: Oxytetracycline reduces the functional diversity of soil microbial community, and the combination of Cu and oxytetracycline leads to a further reduction. AbstractThere are increasing concerns over the effects of veterinary antibiotics and heavy metals in agricultural soils. The widely used veterinary antibiotic oxytetracycline (OTC), Cu and their combination on soil microbial community function were assessed with the Biolog method. The microbial community was extracted from the soil and exposed to a 0.85% sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(94 citation statements)
references
References 45 publications
(47 reference statements)
5
86
1
2
Order By: Relevance
“…Low oxytetracycline concentration (11 μM) might have significant effects on the microbial community in solution (Kong et al 2006). In the present study, the two tested antibiotics were directly spiked into soil, and less inhibitory effectiveness on soil microbial community function was found.…”
Section: Sulfamethoxazole Effect On Functional Diversitymentioning
confidence: 67%
See 2 more Smart Citations
“…Low oxytetracycline concentration (11 μM) might have significant effects on the microbial community in solution (Kong et al 2006). In the present study, the two tested antibiotics were directly spiked into soil, and less inhibitory effectiveness on soil microbial community function was found.…”
Section: Sulfamethoxazole Effect On Functional Diversitymentioning
confidence: 67%
“…The existence of copper would enhance antibiotic negative effect on functional diversity of soil microbial community (Kong et al 2006). It was also reported that combination of cypermethrin and heavy metals could result in great reduction of functional diversity (Xie et al 2009).…”
Section: Sulfamethoxazole Effect On Functional Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Leaching is an-other possible consequence of metal accumulation in soils, mainly after long periods (~20 years) of irrigation with wastewater (Xu et al, 2010). Moreover, accumulated metals may interact synergistically with other contaminants, such as antibiotics, exacerbating their potential effects (Kong et al, 2006;Peltier et al, 2010). Boron is a semi-metallic element and also a pollutant commonly present in wastewater (EPA, 2012;WHO, 2006a).…”
Section: Contaminantsmentioning
confidence: 99%
“…Antimicrobial compounds in soils may disturb the structure and activity of microbial communities (Ding and He, 2010;Kong et al, 2006;Liu et al, 2012;Müller et al, 2002) (Table 3). Indeed, disturbances on N transformation, methanogenesis, and sulphate reduction were reported (Ding and He, 2010).…”
Section: Contaminantsmentioning
confidence: 99%